The Structure and Function of Social Memory in Society - Q. O. Maxkamov (Academicia Globe: Inderscience Research, 2026)
The article is devoted to the analysis of the content, structure and main functions of social memory in society. Also, social memory is interpreted as a set of experience, values, traditions and historical knowledge transmitted from generation to generation and reveals the structural elements of social memory, the relationship between individual memory, group memory and collective memory. In addition, its main functions are highlighted as identification (self-awareness), integration (unification of society), communication (sharing experience) and normativity (regulation of behavior).